Influence of land-use types and topographic slopes on the physico-chemical characteristics of soils in Northwestern Ethiopia - Amare, Hailu; Admase, Habtamu; Ewunetu, Tenagne (Frontiers in Soil Science, 2024)
Aims This study examines the effects of land-use types and slope position on selected soil physico-chemical properties in the Ageza Watershed, Northwestern Ethiopia, focusing on soil fertility depletion and its impact on agricultural productivity. Materials and methods The experiment utilized a randomized complete block design (RCBD) with three replications, involving three land-use types and slope positions. A total of 27 soil samples (both disturbed and undisturbed) were collected, prepared, and analyzed for selected physico-chemical properties following standard laboratory procedures. Data were analyzed using two-way ANOVA with SAS software. Results Significant variations in most soil physico-chemical properties were observed across land-use types and slope positions. Soil bulk density, organic carbon (OC), total nitrogen (TN), available phosphorus (Av. P), cation exchange capacity (CEC), and exchangeable bases significantly (P ≤ 0.001) differed among the land-use types and slope positions. The main effects showed significant (P ≤ 0.05) differences in sand, silt, and clay contents across the land-use types. However, pH did not show significant differences (P > 0.05). Soil bulk density, silt content, Av. P, exchangeable bases, and CEC all showed significant (P ≤ 0.01) differences among the slope positions. Forest land had the highest values for clay (46.11%), OC (6.08%), Av. P (20.60 mg/kg), CEC (33.89 cmol (+) kg-¹), and exchangeable cations: Ca²+ (23.72 cmol (+) kg-¹), Mg²+ (4.40 cmol (+) kg-¹), K+ (1.18 cmol (+) kg-¹), and Na+ (0.77 cmol (+) kg-¹). Grazing land exhibited higher silt and bulk density, while cultivated land had higher sand content. Lower slope positions recorded the highest values for clay (47.33%), silt (20.77%), pH (4.90), Av. P (16.61 mg/kg), Ca²+ (20.10 cmol (+) kg-¹), Mg²+ (3.73 cmol (+) kg-¹), K+ (1.00 cmol (+) kg-¹), Na+ (0.66 cmol (+) kg-¹), and CEC (28.71 cmol (+) kg-¹), while bulk density was higher in the upper slope position. Conclusion Land-use types and slope positions significantly influence variations in soil physico-chemical properties and overall soil fertility status. Forest preservation and management are essential to improve the soil fertility in this region.